Uveal melanoma - testing of abnormalities of chromosome 3 and 8 in the Czech Republic - Matuskova, Veronika; Hornackova, Pavla; Uhmannova, Radoslava; Zlamalikova, Lenka; Liskova, Kvetoslava; Uher, Michal; Vlkova, Eva (Biomedical papers, 2020)
Aim: The aim of this cytogenetic study is to confirm the significance of chromosome 3 loss (monosomy 3) and of the gain of chromosome 8 as prognostic markers in histopathological samples of enucleated eyes with uveal melanoma in the Czech population. Methods: This is a retrospective study of 52 enucleated eyes. Chromosome 3 and 8 status were tested by CISH, and in a few samples FISH was used. The correlation between monosomy 3 and gain of chromosome 8 and clinical features (histopathological type, size of the tumour) were evaluated. A follow up for the detection of metastases was conducted in all patients. The statistical significance of chromosomal abnormalities as a prognostic factor for the development of metastases was calculated. Results: There were 52 patients, 27 men (51.9%) and 25 women (48.1%) enrolled in our study group. The mean age was 63 ± 14 years. Loss of the one copy of chromosome 3 (monosomy 3) was detected in 26 (50.0%) patients, monosomy 8 was present in 34.6% of patients with monosomy 3. After 5 years there were no metastases in 82% of patients without monosomy 3 as opposed to 40% of patients with monosomy 3. We confirmed a statistically significant association between progression free survival (PFS) and the presence of monosomy 3 (P=0.017). The association between PFS and gain of chromosome 8 was significant as well (0.010). Conclusions: Our data showed the association of progression-free survival with the presence of monosomy 3 in uveal melanomas. We provided a good prognostic value of monosomy 3 in uveal melanoma.
Keywords: uveal melanoma; chromosome 3; chromosome 8; CISH; FISH; progression-free survival